Valutazione e Comunicazione del Rischio in Sicurezza Alimentare - Longeri, Maria (Milano University Press, 2023)
Due to its didactic and informative approach, this volume is suitable for those who engage with the topic of risk assessment in food safety for the first time. In the volume, the authors discuss the knowledge and skills that are necessary for effective risk assessment and risk communication and what foundational training courses and economic support one can pursue to gain them. The chapters are written by highly experienced experts. Together, they provide a comprehensive overview of the topic, but they can also be read independently, and each chapter is accompanied by an updated bibliography. The volume is an excellent starting point for specialized insights. It offers an easy general understanding of the topic and of the actions that are being taken by Italy and the European Union to face in a coordinated and effective way the global health challenges of the next years.